Analysis Study of Mentik Wangi Cultivar’s Effect on Technical, Allocative, and Economic Efficiency of Organic Rice Farming in Mojosongo District, Boyolali Regency, Indonesia - Sudrajat, Ignatius Suprih (Canadian Journal of Agriculture and Crops, 2020)
This study is a qualitative and quantitative research that explored about mentik wangi cultivar rice production in organic rice farming system. Mentik wangi cultivar is a local rice seed originating from Magelang Regency, Central Java, which has an advantage in its distinctive aroma that smells naturally nice with a fluffier rice texture, so that it is much sought after by the people of Indonesia. This research aims to analyze the effect of mentik wangi cultivar rice production on technical, allocative and economic efficiency of organic rice farming. The observation was conducted in Dlingo Village, Mojosongo District, Boyolali Regency, Central Java Province, Indonesia. This study was conducted on 216 organic rice farmers as a sample from 521 farmers as a population during two planting seasons with a purposive sampling method. This research uses a stochastic frontier approach on production, cost production and profit function with cross section data. The results of this research are mentik wangi cultivar is the most dominant variable influencing production, production cost and profit efficiency compared to other varieties (IR64 and pandan wangi) with coefficient values of 0.0424, -0.0826, and 0.2159.